2011
DOI: 10.4236/fns.2011.26091
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Gamma Irradiated Beefburger Formulated with Partial Replacement of Beef Fat with Olive Oil and Wheat Bran Fibers

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
2
6
0
1
Order By: Relevance
“…Furthermore, the cis configuration is less stable the trans configuration [35,36]. Similar results were previously observed [37,38]. Irradiating at 5 kGy decreased total amount of USFAs and increased the total amount of SFAs in beef lipids [39].…”
Section: Determination Of Fatty Acid Content In Irradiated and Non-irsupporting
confidence: 88%
“…Furthermore, the cis configuration is less stable the trans configuration [35,36]. Similar results were previously observed [37,38]. Irradiating at 5 kGy decreased total amount of USFAs and increased the total amount of SFAs in beef lipids [39].…”
Section: Determination Of Fatty Acid Content In Irradiated and Non-irsupporting
confidence: 88%
“…[24] It was shown that monounsaturated-rich diet reduced the susceptibility of low density lipoprotein peroxidation and may be of therapeutic value in the treatment of hypercholestrolemia. [25,26] The USFA/SEA index of SKOO which is associated to the impact in the human health is also high (4.93) ( Table 5) which makes them the most suitable edible oils for mass consumption.…”
Section: Fatty Acid Composition Profile Of Syrian Kaissy CV Olive Oimentioning
confidence: 99%
“…This is because most consumers would like to avoid the risks of fat-related diseases including cardiovascular disease, diabetes, obesity, hypertension and some cancers (Singh et al 2011). Reductions in harmful ingredients such as animal fat, salt and phosphates have been investigated for the manufacture of low-fat meat products (Mahmoud and Badr 2011). Hydrocolloids such as carrageenan, konjac and locust bean gum have contributed as fat replacers because of their very low caloric content, inexpensive cost and versatile applications, as they can be added directly or prepared as fat analogues (Choi et al 2008).…”
Section: Introductionmentioning
confidence: 99%